Lords of chaos [videorecording (DVD)] - Åkerlund, Jonas; Åkerlund, Jonas; Culkin, Rory; Cohen, Emory, 1990-; Kilmer, Jack, 1995-; Moynihan, Michael (Unobstructed View, 2019)
Set in Oslo in 1987, seventeen-year-old Euronymous mounts shocking publicity stunts to make his black metal band famous.